Deep integration with the EU and its likely impact on selected ENP countries and Russia - Maryla Maliszewska; Iryna Orlova; Svitlana Taran (Center for Social and Economic Research (CASE), 2009)
The aim of this study is to estimate the impact of the removal of NTBs in trade between the EU and its selected CIS partners: Russia, Ukraine, Georgia, Armenia and Azerbaijan (CIS5). The report includes a discussion of methodologies of measurement of non-tariff barriers and the impact of their removal, including a review of previous studies focusing on CEE and CIS regions. Further, we employ a computable general equilibrium model encompassing the following three pillars of trade facilitation: legislative and regulatory approximation, reform of customs rules and procedures and liberalization of the access of foreign providers of services. We conclude that a reduction of NTBs and improved access to the EU market would bring significant benefits to the CIS5 countries in terms of welfare gains, GDP growth, increases in real wages and expansion of international trade. The possible welfare implications of deep integration with the EU range from 5.8% of GDP in Ukraine to sizeable expected gains in Armenia (3.1%), Russia (2.8%), Azerbaijan (1.8%) and Georgia (1.7%).
Keywords: F13; F14; F15; F17; 330; Institutional harmonization; European integration; European Neighborhood Policy; ENP; non-tariff barriers; NTBs; Computable General Equilibrium; CGE model; Regionale Wirtschaftsintegration; EU-Nachbarstaaten; Institutionelle Infrastruktur; Institutioneller Wandel; Nichttarifäre Handelshemmnisse; Markteintritt; EU-Staaten; Russland; Ukraine; Georgien; Armenien; Aserbaidschan